Enhancing the Mypher Lightweight Cipher Using an LTT-Based Dynamic S-Box for Secure IoT Devices - Purwanto, Eriek Cahyo; Afianti, Farah (Engineering, Technology & Applied Science Research, 2026)
The rapid expansion of Internet of Things (IoT) systems has significantly increased the demand for lightweight cryptographic mechanisms capable of ensuring robust data confidentiality under strict resource constraints, including limited memory, processing power, and energy consumption. Lightweight block ciphers are widely adopted in such environments; however, many existing designs still rely on static Substitution boxes (S-boxes), which introduce fixed substitution patterns that can be analyzed and exploited through linear cryptanalysis. Mypher is a lightweight block cipher designed for efficient operation on resource-constrained devices, yet its security is constrained by the use of a static 4x4 Substitution box (S-box). To address this limitation, this study proposes an enhancement to the Mypher algorithm by integrating a dynamic 4x4 S-box generated using the Linear Trigonometric Transformation (LTT) method. The proposed approach employs key-derived parameters and uses an optimized constant parameter X, selected through a nonlinearity-driven search, to generate highly nonlinear and bijective S-boxes. This optimized X value is consistently applied during both encryption and decryption to ensure correct and efficient implementation. A comprehensive security evaluation of the generated dynamic S-boxes is conducted using standard cryptographic criteria, including bijectivity, Strict Avalanche Criterion (SAC), Bit Independence Criterion (BIC), and nonlinearity analysis. The experimental results demonstrate significant improvements in cryptographic strength compared to the original Mypher and UL-AES S-boxes, indicating increased resistance to linear attacks. Furthermore, the proposed scheme is implemented and evaluated on an ESP32 microcontroller to assess its practical feasibility in real Internet of Things (IoT) environments. Performance measurements show that the integration of the LTT-based dynamic S-box introduces only a modest increase in computational cost, with encryption and decryption times increasing by approximately 7% and 6%, respectively. These results confirm that the proposed LTT-based dynamic S-box significantly enhances the security of Mypher while preserving its lightweight characteristics, making it a practical and effective cryptographic solution for securing data on resource-constrained IoT devices.